1,3,5-Trifluorobenzene - B. S. Hudson, Syracuse University, New York, USA (My University, 2000)
Inelastic Neutron Scattering spectrum of 1,3,5-Trifluorobenzene, C₆H₃F₃, measured on the TFXA instrument.
1,3,5-Trifluorobenzene
Keywords: TFXA